(untitled) (Bulletin of Armenian Libraries, 2025)
The article examines the evidence about Artsakh-Karabakh presented in the bulletins “Reports of the Imperial Archaeological Commission” (“report of the Imperial Archaeological Commission”), one of the many valuable sources stored in the National Library of Armenia. These newsletters were published between 1862 and 1918 once a year, summarizing events from 1859 to 1913-15. the data of the conducted archaeological excavations. 45 volumes of books have been published.